Implementasi Model Atik dalam Meningkatkan Kemampuan Melukis Anak Usia 5-6 Tahun di Masa Pandemi - Mariana, Ana; Watini, Sri; Hulailah Istiqlaliyah (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2022)
This research was conducted to examine learning to paint with the ATIK learning model during the pandemic. The research uses the descriptive-analytical method, which describes the reality of the learning that occurs and how the response of the subject under study is. Primary data sources are 17 students from group B2 in Al Azhar Kindergarten. Secondary data sources journal articles and books that are in accordance with the research discussion. The research findings are the ATIK model, namely the results of children's paintings are much clearer, more shaped, and more colorful. Children become happier in painting activities; they do not hesitate to pour their ideas which are poured into paintings.